2008
DOI: 10.1111/j.1471-4159.2008.05488.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagy precipitates neuronal cell death following low doses of methamphetamine

Abstract: Methamphetamine abuse is toxic to dopaminergic neurons, causing nigrostriatal denervation and striatal dopamine loss. Following methamphetamine exposure, the number of nigral cell bodies is generally preserved, but their cytoplasm features autophagic‐like vacuolization and cytoplasmic accumulation of α‐synuclein‐, ubiquitin‐ and parkin‐positive inclusion‐like bodies. Whether autophagy is epiphenomenal or it plays a role in the mechanism of methamphetamine toxicity and, in the latter case, whether its role cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 56 publications
8
103
2
Order By: Relevance
“…In support of this view, autoptic studies on schizophrenic brains have revealed the presence of neuronal inclusions (see Section 5), which may depend on dysfunctional mTOR-related cell clearing systems. Similarly, neuronal inclusions occur in METH abusers [124], confirming what was previously demonstrated in animal models [125,126]. As detailed in the following paragraph, METH exerts disruptive effects on DA neurotransmission, which translate into abnormal stimulation of post-synaptic DA receptors, mainly D1-type DA receptors (D1R), thus leading to non-canonical signaling cascades sustaining behavioral alterations that overlap with schizophrenia-like symptoms (i.e., visual and auditory hallucinations and delusions) [127,128,129,130].…”
Section: Beyond Classic Neurodegenerationsupporting
confidence: 83%
“…In support of this view, autoptic studies on schizophrenic brains have revealed the presence of neuronal inclusions (see Section 5), which may depend on dysfunctional mTOR-related cell clearing systems. Similarly, neuronal inclusions occur in METH abusers [124], confirming what was previously demonstrated in animal models [125,126]. As detailed in the following paragraph, METH exerts disruptive effects on DA neurotransmission, which translate into abnormal stimulation of post-synaptic DA receptors, mainly D1-type DA receptors (D1R), thus leading to non-canonical signaling cascades sustaining behavioral alterations that overlap with schizophrenia-like symptoms (i.e., visual and auditory hallucinations and delusions) [127,128,129,130].…”
Section: Beyond Classic Neurodegenerationsupporting
confidence: 83%
“…The identification of LC3 as a major component of Lewy bodies raises the possibility that Lewy bodies, which origin and significance are currently unknown, may derive from accumulated undegraded AP. Further supporting the latter possibility, (1) ultrastructural studies indicate that membrane-limited AP can evolve into more mature condensed inclusion bodies, more closely resembling Lewy bodies, in which no longer membranous structures appear (Castino et al, 2008); (2) some pathological studies remarked the rather vesicular nature of Lewy bodies in PD, suggesting the participation of the autophagylysosomal pathway in the formation of these inclusions (Forno and Norville, 1976); (3) nigral Lewy bodies are closely associated with neuromelanin granules, the latter arising from incompletely degraded AP (Tribl et al, 2006); (4) ubiquitin, which is a main component of Lewy bodies and is commonly associated with proteasome degradation pathways, can also target cytosolic components for its autophagic degradation (Kim et al, 2008); (5) Lewy bodies contain abnormal mitochondria and autophagyrelated molecules (Shults, 2006); and (6) LC3-II protein levels are also increased in postmortem cortical tissue from patients with Dementia with Lewy bodies (Yu et al, 2009), a disease that exhibits ␣-synuclein-positive Lewy bodies similar to those found in PD. Further supporting a role for defective lysosomal-mediated cellular clearance in Lewy body formation and PD-related cell death, (1) some patients with Gaucher disease, the most common lysosomal storage disorder resulting from the inherited deficiency of the lysosomal enzyme glucocerebrosidase, exhibit clinical parkinsonism and ␣-synuclein-immunoreactive Lewy bodies (Aharon-Peretz et (Ramirez et al, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…112,126 Indeed, in some cases, autophagosome accumulation detected by TEM does not correlate well with the amount of LC3-II (Tallóczy Z, de Vries RLA, Sulzer D, unpublished results; Eskelinen E-L, unpublished results). This is particularly evident in those cells that show low levels of LC3-II (based on western blotting) because of an intense autophagy flux that consumes this protein, 127 or in cell lines having high levels of LC3-II that are tumor-derived, such as MDA-MB-231.…”
mentioning
confidence: 99%